ANALISIS PENINGKATAN KINERJA JALAN LINGKUNGAN DI KECAMATAN DENPASAR BARAT - Ida Bagus Wirahaji; I Putu Laintarawan; Pande Made Bhanu Waradhya (WidyaTeknik, 2026)
For residents of Denpasar City living in residential or settlement areas, improving the performance of neighborhood roads is essential, as these roads serve as the primary access supporting daily mobility. West Denpasar is the most densely populated district in Denpasar City and contains a large proportion of slum settlement areas. This study aims to analyze community perceptions regarding efforts to improve the performance of neighborhood roads. The study involves four independent variables with 20 indicators. Perception data were collected through questionnaires distributed in West Denpasar District, with a total of 255 valid responses obtained. Data were analyzed using multiple linear regression. The results indicate that all independent variables have a positive and significant effect on neighborhood road performance, with the regression model expressed as Y = 1.114 + 0.169X₁ + 0.446X₂ + 0.334X₃ + 0.371X₄. Based on the regression coefficients, improvement of road supporting facilities (X₂) has the greatest influence, followed by traffic management (X₄), pavement improvement (X₃), and geometric road improvement (X₁). The Adjusted R² value of 94.9% indicates that the independent variables collectively have a very strong influence on neighborhood road performance.